2005
DOI: 10.1002/em.20090
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of chromosome aberrations following acute radiation: I, PAINT translocations, dicentrics, rings, fragments, and insertions

Abstract: Chromosome translocations are used to estimate the doses of radiation received following occupational or accidental exposure. Biodosimetry relies on the assumption that translocations are not cell-lethal and persist with little or no loss over time. While translocations do exhibit substantially greater persistence than other aberration types (e.g., dicentrics), there is evidence that translocation frequencies also decline over time, at least following acute doses above 1 Gy. To the extent that translocation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…It has been definitively demonstrated that in the absence of mitogenic stimulation, cells bearing unstable aberrations are preferentially eliminated via apoptosis (Bassi et al 2003;Belloni et al 2008a), though it is unknown whether this also applies to cells bearing ostensibly stable reciprocal translocations. Accordingly, it has been definitively demonstrated that the frequency of unstable aberrations, and to a lesser but still significant extent, the frequency of translocations, are not constant but decline with time from the levels initially observed following radiation exposure (Matsumoto et al 1998;Tucker et al 1997Tucker et al , 2004Tucker et al , 2005, though the frequency of reciprocal translocations may plateau above preirradiation levels following the initial decline. The initial decline may be due at least in part to the co-occurrence of reciprocal translocations with unstable forms of chromosome damage (Tucker 2008).…”
Section: Does Error-prone Dna Repair Results In An Increase In Risk?mentioning
confidence: 96%
“…It has been definitively demonstrated that in the absence of mitogenic stimulation, cells bearing unstable aberrations are preferentially eliminated via apoptosis (Bassi et al 2003;Belloni et al 2008a), though it is unknown whether this also applies to cells bearing ostensibly stable reciprocal translocations. Accordingly, it has been definitively demonstrated that the frequency of unstable aberrations, and to a lesser but still significant extent, the frequency of translocations, are not constant but decline with time from the levels initially observed following radiation exposure (Matsumoto et al 1998;Tucker et al 1997Tucker et al , 2004Tucker et al , 2005, though the frequency of reciprocal translocations may plateau above preirradiation levels following the initial decline. The initial decline may be due at least in part to the co-occurrence of reciprocal translocations with unstable forms of chromosome damage (Tucker 2008).…”
Section: Does Error-prone Dna Repair Results In An Increase In Risk?mentioning
confidence: 96%
“…The frequency of stable translocations is thought to increase with age because they are induced throughout life and undergo little negative selection during mitosis [33,39,40]. However, the reason(s) translocation frequencies increase in a curvilinear manner is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Some cells were cultured for as long as 72 hours. Although these cultures will contain many cells in their second division, this should not have a large effect on the translocation yield because translocation frequencies in cultured human peripheral blood lymphocytes do not show major changes during the first 72 hours [33].…”
Section: Blood Sample Collection and Culture Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, chromosome translocations are compatible with cell survival. For this reason they show much greater persistence through cell division [21,22] and consequently their frequencies are believed to integrate the effect of chronic exposure [23-25]. Thus, while PCE exposure is of concern to human health, investigations of possible cumulative genetic damage resulting from exposure are lacking.…”
Section: Introductionmentioning
confidence: 99%